Enhancing Operational Efficiency in XYZ Coop: A Six Sigma Approach - Abdul Jalal, Afizah (JBS Nexus, 2025)
XYZ Coop, a cooperative-owned Islamic pawnbroking business in Johor, provides gold pawning services to members and non-members as an alternative source of short-term financing. While the operation has achieved stable revenue and high customer repayment rates, it faces operational challenges in accurately authenticating gold items, exposing the cooperative to risks of counterfeit gold, financial loss, and diminished customer trust. This article examines how the Six Sigma methodology, particularly the DMAIC (Define, Measure, Analyze, Improve, Control) framework, can enhance operational efficiency and gold authentication accuracy at XYZ Coop. Using root cause analysis tools such as the Fishbone diagram and data-driven performance baselines, the study identifies key inefficiencies stemming from a lack of staff training, outdated testing methods, and inconsistent procedures. A structured implementation plan is proposed, incorporating staff training, process optimization, and continuous monitoring. Expected outcomes include improved gold authentication accuracy exceeding 99%, reduced process cycle times, and enhanced customer satisfaction. The findings highlight how service-oriented cooperatives can leverage quality management techniques traditionally used in manufacturing to improve operational performance, reduce risk, and sustain member trust. This case study provides practical insights for similar cooperatives seeking to strengthen governance and efficiency through structured improvement methodologies.